A global survey exploring tackle training knowledge, attitudes and practices of women's rugby union coaches - Dane, K.; West, S. W.; Hendricks, S.; Stodter, A.; Yeomans, C.; van Dyk, N.; Griffin, S.; Wilson, F. (International Journal of Sports Science & Coaching, 2024)
The coaching and performance context in women's rugby is not well understood, despite growing popularity worldwide. The aim of this study was to describe the knowledge, attitudes and tackle training practices of women's rugby coaches in relation to tackle safety and performance. A globally distributed online survey exploring coaches` knowledge, attitudes and practices towards tackling women's rugby was completed by 357 coaches (mean age 41 ± 0.6 years) from 58 countries. The cross-sectional survey was distributed from March 2023 to June 2023. Survey development was guided by the Health Action Process Approach and informed by coaching experts, research evidence synthesis, and guidelines for international tackle safety programmes. Coaches believed that the risk of tackle injury in women's rugby is high and that proper tackle technique for safety is very important. More than 75% of coaches had never completed a tackle-specific training course, with only 39% aware of the availability of such courses. Time spent on controlled-contact and full-contact activities varied from 0 to 40+ min per week, averaging 10-20 min for both types of training. Barriers to the effectiveness of tackle training related to sociocultural factors, coach knowledge gaps, training environments, and player training considerations. Coach education, improved infrastructures, and physical development were ranked the highest priorities for improving tackle safety and performance. These findings inform future implementation strategies for tackle safety and performance in the context of women's rugby, highlighting the need to involve coaches in providing practical solutions, and the role of education and institutional/organisational support in facilitating such improvements.